Hepatitis B and D virus entry - Watashi, Koichi; Shionoya, Kaho; Kobayashi, Chisa; Morita, Takeshi (Nature reviews. Microbiology, 2025)
Hepatitis B virus (HBV) entry is the initial step of viral infection, leading to the formation of covalently closed circular DNA, which is a molecular reservoir of viral persistence and a key obstacle for HBV cure. The restricted entry of HBV into specific cell types determines the nature of HBV, which has a narrow host range in tissues and species. Hepatitis D virus (HDV) shares viral surface antigens with HBV and thus follows a similar entry mechanism at its early stages. In late 2012, sodium taurocholate cotransporting polypeptide was discovered as an HBV and HDV entry receptor. Since then, the mechanisms of HBV and HDV entry have been extensively analysed. These analyses have expanded our understanding of HBV and HDV host tropism and have provided new strategies for the development of antiviral agents. Notably, the structures of sodium taurocholate cotransporting polypeptide and its interaction with the 2-48 amino acid region of viral preS1 have been recently solved. These findings will stimulate further entry studies. In this Review, we summarize current understanding of HBV and HDV entry and future perspectives.